2014
DOI: 10.1093/mnras/stt2327
|View full text |Cite
|
Sign up to set email alerts
|

Teasing bits of information out of the CMB energy spectrum

Abstract: Departures of the Cosmic Microwave Background (CMB) frequency spectrum from a blackbody -commonly referred to as spectral distortions -encode information about the thermal history of the early Universe (redshift z few×10 6 ). While the signal is usually characterized as µ-and y-type distortion, a smaller residual (non-y/non-µ) distortion can also be created at intermediate redshifts 10 4 z 3 × 10 5 . Here, we construct a new set of observables, µ k , that describes the principal components of this residual dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
217
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(221 citation statements)
references
References 101 publications
3
217
0
Order By: Relevance
“…Although the dissipation-induced average y distortion is expected to be 5 times smaller than the µ distortion (see estimate above), the experimental sensitivity to y is 5 − 10 times better [42,44]. Assuming a PRISM detection limit of y min 2 × 10 −10 , we thus infer a comparable smallest nonGaussianity parameter, …”
mentioning
confidence: 73%
“…Although the dissipation-induced average y distortion is expected to be 5 times smaller than the µ distortion (see estimate above), the experimental sensitivity to y is 5 − 10 times better [42,44]. Assuming a PRISM detection limit of y min 2 × 10 −10 , we thus infer a comparable smallest nonGaussianity parameter, …”
mentioning
confidence: 73%
“…The other constraints are described in the main body of the text. The reach of PIXIE corresponds to µ < 2.8 × 10 −8 and y < 2.4 × 10 −9 [63,64]. The reach including the expected impact of foregrounds, µ < 9.4 × 10 −8 [65], is shown with a dotted line.…”
mentioning
confidence: 99%
“…7). As we discuss later, any detection of such values of µ-distortions will rule out single-field slow-roll inflation, if we assume that all the generated distortions are due to Silk damping and not to other mechanisms like, for example, decaying Dark Matter particles; 7 6 In [45] it was shown that, when also r-distortions are considered, the expected error should be larger (about σµ = 1.4 × 10 −8 ): however at the large values of αs and βs allowed by Planck, the forecasts of Tab. VI are not significantly affected.…”
mentioning
confidence: 99%